How does Creative Industry Innovation affect Entrepreneurial Interest Mediated by Student Entrepreneurial Motivation? - Rini Ariyanti; Ahmad Fathir Imran; Anis Pri Nandini; Muh. Fadil Nugraha; Gleno Amdalitu Tandi (Indonesian Journal of Business and Entrepreneurship Research, 2024)
This study investigates the impact of creative industry innovation on the entrepreneurial interest of University of Makassar students, with entrepreneurial motivation as a mediator. According to the latest survey on creative economy, this industry has shown significant growth in its contribution to national GDP. However, entrepreneurial interest is still considered low among students, despite having great potential. Through regression analysis, the findings show that creative industry innovation has a positive and significant influence on entrepreneurial interest among students, both directly and through entrepreneurial motivation as a mediator. The implications of these findings are the need for increased understanding and awareness of the importance of innovation in promoting entrepreneurial interest among students, by involving various parties such as educational institutions, government, and the creative industry.